2021
DOI: 10.1590/1981-86372021002220190095
|View full text |Cite
|
Sign up to set email alerts
|

Important aspects during advanced lingual laceration management: report of 2 cases

Abstract: Intraoral injuries affect the stomatognathic system, creating difficulties in mastication and speech articulation, especially when they affect the tongue. In this context, the quality of the suture and local care are important to proper recovery and the patient’s brief return to their normal functions. Oral lacerations resulting from trauma require specific approaches. Treatments of this type of trauma may primarily be performed by professionals who conduct emergency care; however, they may require the attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The effects of mouthguards for trauma prevention and reduction have been well recognized. 1 2 3 4 5 6 7 8 9 As a valuable epidemiological study, the ADA Council reported the mouthguards' value in reducing sports-related injuries to the teeth and soft tissues. 7 Further, Fernandes et al 1 revealed in their review that the prevalence of dentoalveolar trauma among mouthguard users was 7.5%, while the prevalence among non-users was 59.48%, in top quality problem-free studies.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of mouthguards for trauma prevention and reduction have been well recognized. 1 2 3 4 5 6 7 8 9 As a valuable epidemiological study, the ADA Council reported the mouthguards' value in reducing sports-related injuries to the teeth and soft tissues. 7 Further, Fernandes et al 1 revealed in their review that the prevalence of dentoalveolar trauma among mouthguard users was 7.5%, while the prevalence among non-users was 59.48%, in top quality problem-free studies.…”
Section: Introductionmentioning
confidence: 99%